AN EMPIRICAL STUDY ON THE USAGE OF DIGITAL BANK IN INDONESIA - Fatimah, Siti; Oktaviana, Rina (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
This research was conducted to determine the existence of a bond between self-esteem and body image in adolescents at Tanjung Barangan, Palembang. The hypothesis put forward in this study is that there is a relationship between self-esteem and body image in adolescents in TanjungBarangan, Palembang. The sample in this research was 190 teenagers in rt. 002-003 at TanjungBarangan, Palembang city. The sample technique used in this research is simple random sampling technique. Measuring tool used is a scale of self-esteem and body image. The analysis technique used is simple regression using SPSS version 20.0. The results of the analysis show that the correlation coefficient (r) = 0.462 with the score obtained is (R-square) = 0.213 and p = 0.000 (p <0.05 and p <0.01) which means that the proposed hypothesis is accepted. These results indicate that there is a very significant relationship between self-esteem and body image in adolescents from rt. 002-003 at TanjungBarangan, Palembang city. The contribution of the self-esteem variable to the body image variable is 21.3%.